PREVELANCE OF ADMISSION HYPOTHERMIA AMONG VERY LOW BIRTH WEIGHT NEONATES (Journal of Medical & Health Sciences Review, 2025)
Objective: To determine the frequency of admission hypothermia among VLBW neonates within the first 24 hours of life. Methodology: A descriptive cross-sectional study was conducted from January 2025 to June 2025 after taking ethical approval from institutional ethical review board (124/IRB/SZMC/SZH) and informed consent from parents or guardian at pediatric ward of Sheikh Zayed Medical College/Hospital Rahim Yar Khan. A total of 160 VLBW neonates (